Aqueous two-phase systems formed by biocompatible and biodegradable polysaccharides and acetonitrile - Cardoso, Gustavo de Brito
In this work, it is shown that novel aqueous two-phase systems can be formed by the combination of acetonitrile and polysaccharides, namely dextran. Several ternary phase diagrams were determined at 25 degrees C for the systems composed of water + acetonitrile + dextran. The effect of the dextran molecular weight (6000, 40,000 and 100,000 g mol(-1)) was ascertained toward their ability to undergo liquid-liquid demixing. An increase in the dextran molecular weight favors the phase separation. Furthermore, the effect of temperature (25, 35 and 45 degrees C) was evaluated for the system constituted by the dextran of higher molecular weight. Lower temperatures are favorable for phase separation since lower amounts of dextran and acetonitrile are required for the creation of aqueous two-phase systems. In general, acetonitrile is enriched in the top phase while dextran is majorly concentrated in the bottom phase. The applicability of this new type of two-phase systems as liquid-liquid extraction approaches was also evaluated by the study of the partition behavior of a well-known antioxidant - vanillin - and used here as a model biomolecule. The optimized conditions led to an extraction efficiency of vanillin of 95% at the acetonitrile-rich phase. (C) 2014 Elsevier B.V. All rights reserved.